An Efficient and Cost-Effective Method for Preparing Transmission Electron Microscopy Samples from Powders. (9th September 2015) - Wen, Haiming; Lin, Yaojun; Seidman, David N.; Schoenung, Julie M.; van Rooyen, Isabella J.; Lavernia, Enrique J.
Abstract: The preparation of transmission electron microcopy (TEM) samples from powders with particle sizes larger than ~100 nm poses a challenge. The existing methods are complicated and expensive, or have a low probability of success. Herein, we report a modified methodology for preparation of TEM samples from powders, which is efficient, cost-effective, and easy to perform. This method involves mixing powders with an epoxy on a piece of weighing paper, curing the powder–epoxy mixture to form a bulk material, grinding the bulk to obtain a thin foil, punching TEM discs from the foil, dimpling the discs, and ion milling the dimpled discs to electron transparency. Compared with the well established and robust grinding–dimpling–ion-milling method for TEM sample preparation for bulk materials, our modified approach for preparing TEM samples from powders only requires two additional simple steps. In this article, step-by-step procedures for our methodology are described in detail, and important strategies to ensure success are elucidated. Our methodology has been applied successfully for preparing TEM samples with large thin areas and high quality for many different mechanically milled metallic powders.